2012
DOI: 10.1155/2012/838496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Intensity Laser Irradiation on Wound Healing in Diabetic Rats

Abstract: Objective. The effects of low-intensity 630 nm semiconductor laser irradiation at 3.6 J/cm 2 (LISL) on wound healing in diabetic rats were studied in this paper. Methods. 36 diabetic rats with dorsal cutaneous excisional wounds were divided into three LISL groups and a control group randomly. The three LISL groups were irradiated with LISL at 5, 10, and 20 mW/cm 2 five times a week for two weeks, respectively. The process of wound healing was assessed by assessing blood glucose, calculating percentage of wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…In a study 25 that compared the LPL irradiation at a dose of 3.6 J/cm 2 in different powers: 5 mW/cm 2 (12 min), 10 mW/ cm 2 (6 min) and 20 mW/cm 2 (3 min), applied 5 times/week for two weeks, showed that, generally the larger laser irradiation powers were more effective and significant for the quality of the cicatrization process, according to some histological criteria, such as collagen synthesis, proliferation of fibroblasts, epithelialization, quantity of polymorphonuclear and neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…In a study 25 that compared the LPL irradiation at a dose of 3.6 J/cm 2 in different powers: 5 mW/cm 2 (12 min), 10 mW/ cm 2 (6 min) and 20 mW/cm 2 (3 min), applied 5 times/week for two weeks, showed that, generally the larger laser irradiation powers were more effective and significant for the quality of the cicatrization process, according to some histological criteria, such as collagen synthesis, proliferation of fibroblasts, epithelialization, quantity of polymorphonuclear and neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al found that LIL promoted the healing of the wound of STZ-induced diabetes of male Wistar rats before 9th day, but did not on 14th day. As a fact, even type 2 diabetes might be self-limited [66]. Lim et al found that normalisation of both beta cell function and hepatic insulin sensitivity in type 2 diabetes was achieved by dietary energy restriction alone [67].…”
Section: Successful Stress Dpbm Cannot Modulate a Successfulmentioning
confidence: 99%
“…For example, Ezzati et al investigated the influence of pulsed LLLT on the healing of a third-degree burn in a rat model, and it significantly increased wound closure rate [15]. Some recent studies indicated that laser effectively improved the healing of third-degree burns in diabetic rats [15,25,28]. Other studies suggest that laser irradiation accelerates wound healing of the pulp and the expression of collagens.…”
Section: Discussionmentioning
confidence: 99%